The Role of Non-coding RNAs in Viral Myocarditis - Zhang, Cong; Xiong, Yan; Zeng, Lijin; Peng, Zhihua; Liu, Zhihao; Zhan, Hong; Yang, Zhen (Frontiers in Cellular and Infection Microbiology, 2020)
Viral myocarditis (VMC) is a disease characterized as myocardial parenchyma or interstitium inflammation caused by virus infection, especially Coxsackievirus B3 (CVB3) infection, which has no accurate noninvasive examination for diagnosis and specific drugs for treatment. The mechanism of CVB3-induced VMC may be related to direct myocardial damage of virus infection and extensive damage of abnormal immune response after infection. Non-coding RNA (ncRNA) refers to RNA that is not translated into protein and plays a vital role in many biological processes. There is expanding evidence to reveal that ncRNAs regulate the occurrence and development of VMC, which may provide new treatment or diagnosis targets. In this review, we mainly demonstrate an overview of the potential role of ncRNAs in the pathogenesis, diagnosis and treatment of CVB3-induced VMC.